Pengaruh Struktur Kepemilikan, Karakteristik Perusahaan dengan Struktur Modal dan Kinerja Keuangan sebagai Variabel Intervening Terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Pertambangan yang Terdaftar di BEI pada Tahun 2020-2022 - Audreyna Missel, Rheinata; Hwihanus (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study analyzes manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022, with ten companies purposively selected. The objective is to examine the effect of ownership structure, business characteristics, and capital structure on firm value, with financial performance as a moderating variable. Data was taken from the IDX annual financial reports and analyzed using Smart PLS. The results show that firm characteristics have a significant effect on financial performance, but not on value or capital structure. Financial performance affects capital structure, but has no direct effect on firm value. The findings provide insights for investors and industry players on the effect of financial performance and capital structure on firm value.